The Evaluation of Prognostic Value and Immune Characteristics of Ferroptosis-Related Genes in Lung Squamous Cell Carcinoma - Su, Jialin; Tan, Shuhua; Gong, Houwu; Luo, Yongzhong; Cheng, Tianli; Yang, Hua; Wen, Xiaoping; Jiang, Zhou; Li, Yuning; Zhang, Lemeng (Global Medical Genetics, 2023)
Background The purpose of our study was to construct a prognostic model based on ferroptosis-related gene signature to improve the prognosis prediction of lung squamous carcinoma (LUSC).Methods The mRNA expression profiles and clinical data of LUSC patients were downloaded. LUSC-related essential differentially expressed genes were integrated for further analysis. Prognostic gene signatures were identified through random forest regression and univariate Cox regression analyses for constructing a prognostic model. Finally, in a preliminary experiment, we used the reverse transcription-quantitative polymerase chain reaction assay to verify the relationship between the expression of three prognostic gene features and ferroptosis.Results Fifty-six ferroptosis-related essential genes were identified by using integrated analysis. Among these, three prognostic gene signatures (HELLS, POLR2H, and POLE2) were identified, which were positively affected by LUSC prognosis but negatively affected by immune cell infiltration. Significant overexpression of immune checkpoint genes occurred in the high-risk group. In preliminary experiments, we confirmed that the occurrence of ferroptosis can reduce three prognostic gene signature expression.Conclusions The three ferroptosis-related genes could predict the LUSC prognostic risk of antitumor immunity.
Keywords: lung squamous carcinoma; ferroptosis; prognostic model; immune infiltration; antitumor immunity